TLR3 Activation of Hepatic Stellate Cell Line Suppresses HBV Replication in HepG2 Cells - Zhang, Biao; Liu, Yu; Wang, Xu; Li, Jieliang; Xu, Xiqiu; Guo, Le; Ho, Wen-Zhe (Frontiers in Immunology, 2018)
There is limited information about the role of hepatic stellate cells (HSCs) in the liver innate immunity against hepatitis B virus (HBV) infection. We thus examined whether hepatic stellate cell line (LX-2) can be immunologically activated and produce antiviral factors that inhibit HBV replication in HepG2 cells. We found that LX-2 cells expressed the functional Toll-like receptor 3 (TLR3), activation of which by PolyI:C resulted in the selective induction of interferon-β (IFN-β) and IFN-λs, the phosphorylation of IFN regulatory factor 3 (IRF3) and IRF7. When HepG2 cells were treated with supernatant (SN) from PolyI:C-activated LX-2 cells, HBV replication was significantly inhibited. IFN-β and IFN-λ appeared to contribute to LX-2 SN-mediated HBV inhibition, as the antibodies to IFN-β and IFN-λ receptors could largely block the LX-2 SN action. Mechanistically, LX-2 SN treatment of the HepG2 cells induced a number of antiviral IFN-stimulated genes (ISGs: ISG20, ISG54, ISG56, OAS-1, Trim22, and Trim25) and facilitated the phosphorylation of STATs. These observations support further studies on the role of HSCs in the liver innate immunity against HBV infection.